The Effect of Supply Chain Integration on Operational Performance and Product Quality - Setyadi, Antonius (Dinasti International Journal of Digital Business Management, 2023)
PT XYZ Indonesia is a company that has shown outstanding business performance in the last three years, and it has grown yearly. A study was conducted by distributing 40 questionnaires that became samples of company employees with work relationships and knowledge of supply chain integration, operational performance, and product quality to test these hypotheses. Furthermore, the data were analyzed with an SEM tool to test the causality relationship of the research variables. The theoretical evidence showed that product quality is positively influenced by supply chain integration for this type of company's business field. The managerial implications are to pay more attention to supply chain integration which greatly affects the company's operational performance. Meanwhile, some limitations in this study can be found at the end of the discussion.